Influence of Control Structures and Load Parameters on Performance of a Pseudo Direct Drive - Mohammed Bouheraoua; Jiabin Wang; Kais Atallah (Machines, 2014)
The paper describes an in-depth and systematic analysis of a pseudo direct drive permanent magnet machine in closed loop control. Due to the torque being transmitted from the high-speed rotor (HSR) to the low-speed rotor (LSR), through a relatively low stiffness magnetic gear with non-linear characteristics, speed oscillations appear in the drive output with a conventional proportional integral (PI) controller. Therefore two candidate controllers have been proposed as an alternative to the PI control and all controllers have been optimally tuned with a genetic algorithm against a defined criterion. Furthermore, closed loop models are established in the complex frequency domain to determine the system damping and the cause of the oscillations. Consequently, the best controller structure that improves the dynamic behaviour of the system in terms of speed tracking and disturbance rejection could be identified, based on the frequency domain analysis. Experimental results are presented to validate the analysis and the proposed control technique.